Simulasi Protokol Routing AODV untuk Skenario Mobilitas Node - Muhammad Akbar Farisi; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Mobile Ad-Hoc Network (MANET) is one of the example of technology development in networking. In MANET there are nodes that has mobility and communicate with each other through wireless network. In order to communicate in MANET, there need to be routing protocol that can be used, and the most commonly used is Ad-Hoc on Demand Distance Vector (AODV). And live up to its name, AODV is a protocol that has a dynamic topology, and it fits right in for MANET conditions. Therefore, with those conditions, there's a need to conduct study if number and mobility of nodes will affect performance of AODV in MANET. This study aims to understand and analyze the performance of AODV in MANET if there's a change in number and mobility of nodes. On this study there will be 2 categories of special scenarios will also be conducted with difference in number of nodes and node speed. So the special scenarios are 2 node and 10 nodes with (20, 40, 60, 80, 100 m/s) for the speed of nodes. Through this study, the results are adding number of nodes from 2 to 10 nodes definitely affected the performance of AODV. The scenarios with 2 nodes show better results than the 10 nodes ones, because with more nodes it takes more time to find the route for sending packets. And with speed variation, it also affected the performance, as the faster the nodes, the harder it becomes to find a route with stability, as it shows on packet delivery ratio that keeps dropping.